2006
DOI: 10.1002/mus.20512
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic reticulum: The dynamic calcium governor of muscle

Abstract: The sarcoplasmic reticulum (SR) provides feedback control required to balance the processes of calcium storage, release, and reuptake in skeletal muscle. This balance is achieved through the concerted action of three major classes of SR calcium-regulatory proteins: (1) luminal calcium-binding proteins (calsequestrin, histidine-rich calcium-binding protein, junctate, and sarcalumenin) for calcium storage; (2) SR calcium release channels (type 1 ryanodine receptor or RyR1 and IP3 receptors) for calcium release; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
150
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(156 citation statements)
references
References 200 publications
(226 reference statements)
1
150
0
2
Order By: Relevance
“…As reviewed by Rossi and Dirksen (2006), developmental studies have shown that SAR exhibits a gradual increase during fibre maturation in both skeletal and smooth muscle. The biochemical Comparative immunoblot analysis of key Ca 2+ -handling proteins in young adult, adult and senescent rat skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reviewed by Rossi and Dirksen (2006), developmental studies have shown that SAR exhibits a gradual increase during fibre maturation in both skeletal and smooth muscle. The biochemical Comparative immunoblot analysis of key Ca 2+ -handling proteins in young adult, adult and senescent rat skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ca 2+ -extrusion is mediated by the surface Na + /Ca 2+ -exchanger (NCX) and the plasmalemmal Ca 2+ -ATPase (PMCA). A physiological mediator between Ca 2+ -release and Ca 2+ -uptake is represented by the luminal SR Ca 2+ -reservoir system made up of calsequestrin (CSQ), sarcalumenin (SAR), junctate and related Ca 2+ -binding proteins (Rossi and Dirksen, 2006 (Leberer et al, 1990). Previous aging studies suggest that no major changes occur in SR protein expression levels in skeletal muscle, as reviewed by Margreth et al, 1999.…”
Section: Introductionmentioning
confidence: 99%
“…In the skeletal muscle, the sarcoplasmic reticulum (SR) functions as a dynamic Ca 2+ governor that provides automatic feedback control for altering and maintaining myoplasmic and SR Ca 2+ levels [50,51]. One of the proteins involved in Ca 2+ transport is the sarcoendoplasmic reticulum Ca 2+ -ATPase (SERCA) [52].…”
Section: Sercamentioning
confidence: 99%
“…As a result of cross bridge cycling, actin filaments are pulled toward the center of the sarcomere, the sarcomere shortens, and the muscle contracts and generates force. The process is finally reversed upon cessation of calcium release following membrane repolarization and the subsequent reuptake of calcium into the SR through the activity of SR calcium ATPases (SERCAs) [3]. In addition to EC coupling, the triad also participates in the regulation of calcium homeostasis, which, in turn, regulates key cellular process such as oxidative stress, autophagy, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%